2000
DOI: 10.1046/j.1432-1327.2000.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of enzymes that repair endogenous damage to DNA

Abstract: A significant contribution to human mutagenesis and carcinogenesis may come from DNA damage of endogenous, rather than exogenous, origin. Efficient repair mechanisms have evolved to cope with this. The main repair pathway involved in repair of endogenous damage is DNA base excision repair. In addition, an important contribution is given by O 6 -alkylguanine DNA alkyltranferase, that repairs specifically the miscoding base O 6 -alkylguanine. In recent years, several attempts have been carried out to enhance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 200 publications
(247 reference statements)
5
76
0
1
Order By: Relevance
“…ERCC6 functions in DNA repair, regardless of whether the repair is transcription coupled or base incision, as a partner in protein complexes (30,40). It has been reported that overexpression of just one element in an enzyme complex can adversely affect the desired end result (41)(42)(43)(44)(45). Even though a statistically identified epistasis does not necessarily mean a biological epistasis (24), prolonged enhanced expression of ERCC6 could result in significant biological epistasis because ERCC6 is known to play an important role in universal transcription by functioning as a component of RNA pol I transcription complex (40).…”
Section: Discussionmentioning
confidence: 99%
“…ERCC6 functions in DNA repair, regardless of whether the repair is transcription coupled or base incision, as a partner in protein complexes (30,40). It has been reported that overexpression of just one element in an enzyme complex can adversely affect the desired end result (41)(42)(43)(44)(45). Even though a statistically identified epistasis does not necessarily mean a biological epistasis (24), prolonged enhanced expression of ERCC6 could result in significant biological epistasis because ERCC6 is known to play an important role in universal transcription by functioning as a component of RNA pol I transcription complex (40).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Carcinomas result from a progressive accumulation of multiple genetic changes in cells, 13 and there is increasing evidence that endogenous DNA damage is a major etiological factor in human cancers. 14,15 At low concentrations, reactive oxygen species (ROSs) act as intra and intercellular second messengers modulating cellular functions including proliferation, apoptosis and gene expression. 16 When ROSs are produced in excess, as in macrophages and polymorphonuclear cells with microbial infections, 17 they are able to induce oxidatively generated DNA damage, 18 an independent risk factor for cancer often involving p53 gene mutations in humans.…”
mentioning
confidence: 99%
“…7,8 The threat to genome integrity represented by oxidized purines could be reduced in human cells by expression of efficient repair activities obtained from heterologous sources. 9 The E. coli formamidopyrimidine DNA glycosylase (FPG) protein differs from hOGG1 under several aspects. hOGG1 only excises from DNA 8-oxoG and FapyG, while FPG fastly releases 8-oxoG, FapyG and FapyA with similar excision kinetics.…”
mentioning
confidence: 99%